2019
DOI: 10.21203/rs.2.12393/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the Hypothetical Constructs of Knowledge, Attitude, and Practices regarding Dengue in Selangor, Malaysia

Abstract: Background: Knowledge, attitude, and practice (KAP) on dengue are hypothetical constructs which are substantiated through the set of composed questions. KAP on dengue is one of the most economical and effective methods used to curtail the incidence of dengue fever because of the absence of efficient vaccines with considerable contraindications and certified chemoprophylaxis for the infection in the affected regions of the world. Methods: A cross-sectional study was carried out with the use of a validated struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 9 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Systematic reviews of observational studies or those related to knowledge assessment have been known to suffer from a high level of heterogeneity among the included primary studies 18,23,24 . This was also observed in the present review and is a major limitation.…”
Section: Discussionmentioning
confidence: 69%
“…Systematic reviews of observational studies or those related to knowledge assessment have been known to suffer from a high level of heterogeneity among the included primary studies 18,23,24 . This was also observed in the present review and is a major limitation.…”
Section: Discussionmentioning
confidence: 69%
“…The present review found 14 studies with moderate to high risks 11,12,15,16,17,20,21,22,24–30,33,34,35 . Future studies in this area must be designed to reduce these biases 19,53–55 …”
Section: Discussionmentioning
confidence: 90%
“…Hence, a protocol for the review was prepared as per PRISMA guidelines and the previous work of other medical specialties. 18,[53][54][55] In terms of geographical distribution, almost 2/3 of the studies regions. There is a need to assess the awareness status in these F I G U R E 4 A, Forest plot.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations